Kajian Pertumbuhan Dan Kelangsungan Hidup Ikan Bubara (Caranx Sp) Di Keramba Jaring Apung Eco Nusa Pulau Gunung Api Desa Nusantara - Kaimudin, Ifandris; Abidin, Jenny (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The Banda Islands are part of the Central Maluku Regency. This region has significant fisheries potential, particularly in aquaculture, and one promising sector to be developed is fish farming using the Floating Net Cage (FNC) system. One of the fish species cultivated in the Floating Net Cage system in the Banda Islands is the Bubara fish (Caranx sp.). This study aimed to determine the growth rate and survival of Bubara fish (Caranx sp.) cultivated in the EcoNusa floating net cages located in Gunung Api Island, Nusantara Village. The benefit of this research is to provide information and serve as a reference for fish farmers in improving the cultivation of Bubara fish in floating net cages. A field survey or quantitative method was employed to obtain preliminary information regarding Bubara fish (Caranx sp.) in the EcoNusa floating net cages at Gunung Api Island, Nusantara Village. The results showed an increase in fish body weight of 2.7 grams during the 30-day rearing period. Based on the weight gain data, the growth rate of Bubara fish during the study was found to be 9%, calculated from the average final weight minus the average initial weight multiplied by 100%.